2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1489.r1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of dorsal screw penetration after volar plating of a distal radial fracture

Abstract: Aims The aim of this study was to investigate whether intraoperative 3D fluoroscopic imaging outperforms dorsal tangential views in the detection of dorsal cortex screw penetration after volar plating of an intra-articular distal radial fracture, as identified on postoperative CT imaging. Methods A total of 165 prospectively enrolled patients who underwent volar plating for an intra-articular distal radial fracture were retrospectively evaluated to study three intraoperative imaging protocols: 1) standard 2D f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The health care cost savings resulting from this practice may be substantial as long screws were present in approximately 25% of constructs. 14 , 15 If an orthopaedic surgeon performs 500 cases per year, then an estimated 125 cases have potential cost savings associated with cutting a screw. For nonlocking cortical screws at $20 per screw, there could be a cost savings of $2,500 per year.…”
Section: Discussionmentioning
confidence: 99%
“…The health care cost savings resulting from this practice may be substantial as long screws were present in approximately 25% of constructs. 14 , 15 If an orthopaedic surgeon performs 500 cases per year, then an estimated 125 cases have potential cost savings associated with cutting a screw. For nonlocking cortical screws at $20 per screw, there could be a cost savings of $2,500 per year.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the ability of this view to detect dorsal long screws leading to change. 22,29,30 Langerhuizen et al 33 compared the combination of DTV, AP and elevated lateral, to standard fluoroscopic imaging (AP and elevated lateral) and 3D fluoroscopy in a total of 165 patients. They found in order to detect dorsal screw penetration, the sensitivity of DTV was 39% with an accuracy of 91% compared with a sensitivity of 25% for 3D fluoroscopy and an accuracy of 93%.…”
Section: Radiological Estimates Of Optimal Screw Lengthmentioning
confidence: 99%
“…Strategies to reduce the incidence of dorsal screw penetration involve the use of Dorsal Tangential Views (DTV) and 3D Fluoroscopy [3,[9][10][11]. These techniques have been reported to decrease dorsal penetration from at least one dorsally penetrating screw in 40% of patients with standard 2D fluoroscopic imaging to 32% with use of DTV intra-operatively, and a further reduction to 25% has been observed using-resource intensive-3D Fluoroscopy intra-operatively [1].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore conducted a cross-sectional diagnostic imaging study on 3D virtual pre-operative planning for intra-articular distal radius fractures to answer the main study question: does pre-operative 3DVP result in an additional reduction of dorsal screw penetration? Pre-operative Computed Tomography (CT) scans from our index prospective cohort [ 1 ] (IPC) were retrospectively used for 3DVP and compared to the corresponding post-operative CTs to assess potential differences in number of dorsal screw penetrations. We aimed to (1) compare 3DVP planned screws versus screws that were placed in the actual operation of the IPC (as measured on post-operative CT) in terms of (a) screw lengths; (b) appropriate screw lengths (defined as within 75–100% of distal radius diameter); and (c) dorsal screw penetration; as well as; (2) evaluate the inter-observer reliability of the chosen 3DVP screw lengths and preferred plate size between three observers.…”
Section: Introductionmentioning
confidence: 99%